1990
DOI: 10.1172/jci114802
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypertrophic cardiomyopathy is a genetically heterogeneous disease.

Abstract: We demonstrate that familial hypertrophic cardiomyopathy (FHC), an autosomal dominant disorder of heart muscle, is a genetically heterogeneous disease. The locus responsible for FHC in members of one large kindred was recently mapped to chromosome 14q11-12 (FHC-1). We have characterized three additional unrelated families in which the gene for FHC segregates as an autosomal dominant trait to determine if these disease loci also map to FHC-1. All family members were clinically studied by physical examination, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(36 citation statements)
references
References 16 publications
0
33
0
3
Order By: Relevance
“…These have all been detected in the head and head-rod junction regions of the f3-MHC protein. The f-MHC gene, however, has been excluded as the disease locus in other kindreds (3,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…These have all been detected in the head and head-rod junction regions of the f3-MHC protein. The f-MHC gene, however, has been excluded as the disease locus in other kindreds (3,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…HCM represents a paradigm ofcardiac pathophysiology and elucidation of its molecular basis should provide information fundamental to our understanding of the biology and pathology of the myocardium. The gene responsible for FHCM has been localized in some families to chromosome 14 (3)(4)(5)(6), and the f3-myosin heavy chain (i3MHC) gene has been identified as the candidate gene for this disease (3)(4)(5). Three mutations in #MHC gene in two families with FHCM have been described.…”
Section: Introductionmentioning
confidence: 99%
“…'-" In some kindreds, the disease has been linked to the f-myosin heavy chain (3-MHC) gene locus on chromosome 14ql. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In these kindreds, HCM has been associated with substitutions of single highly conserved amino acids in the head or head-rod junction of the ,B-MHC molecule. We have previously reported that clinical expression has differed significantly in two kindreds with distinct 3-IMHC gene mutations: The 908``u va1 mutation has been associated with low disease penetrance and a benign prognosis.…”
mentioning
confidence: 99%